전문직 종사자에 대한 대중의 온라인 평가와 개인정보자기결정권에 관한 고찰 - 백경희 (원광법학, 36(1), 2020)
IT 기술의 발달로 이제 컴퓨터 네트워크인 온라인을 통하여 형성된 사이버 스페이스(Cyber Space)는 종래 공개적인 표현의 대표적 매개체로 이용되었던 신문이나 잡지와 같은 지면을 대체하게 되었다. 또한 사이버 스페이스에서의 정보의 전달이나 주관적 평가는 그 파급력 역시 지류와는 비교가 되지 않을 정도로 시공간을 초월하는 양상을 띄고 있기에, 표현의 자유가 극대화되는 경향을 가져오기도 하였다. 그러나 한편 사이버 스페이스라는 가상의 공간에서 한 개인의 정보가 본인의 동의 없이 공개되어 인격권이나 프라이버시를 침해하고, 일개인의 주관적 평가가 온라인을 통해 순식간에 확산되어 개인의 명예를 훼손하고 극단적 선택을 촉발시키는 원인이 되는 등 폐해가 속출하고 있다. 최근 우리나라에서 발생한 어린이집 보육교사의 자살 사건에서 나타나듯이, 특수한 영역의 전문직의 경우 높은 공익성과 도덕성을 요구하는 직업이라는 점에서, 사적 개인보다는 공적 개인으로 취급하는 경향이 강하다. 그렇기 때문에 교사를 비롯하여 변호사, 의사와 같이 공익성이 요구되는 전문직 종사자는, 정보주체의 동의가 없더라도 국민의 알 권리를 위하여 개인 정보의 공개와 온라인읕 통한 대중의 주관적 평가 또한 일정 부분 수인하여야 하는 위치에 있다고 보고 있다. 특히 전문직 종사자에 대한 대중의 온라인 평가가 표현의 자유로 보호받을 수 있는 법적 이익인지 및 그로 인하여 침해되는 개인의 인격적 법익은 어떻게 보호될 수 있는지가 우리나라와 독일의 판례에서 문제된 바 있다. 더구나 ‘평가’의 경우 지극히 주관적인 관점이 개재될 수 있고, 온라인에서 대중이나 개개 포털 관리자의 자의적인 기준이 덧대어져 평가가 진행된다면, 그와 같이 산정된 평가 결과를 아무리 공익성을 띄는 전문직에 종사한다고 하더라도 이를 수인하기가 쉽지 않다. 또한 인터넷의 경우 매체가 지니는 특수성으로 인하여 확산 가능성과 전문직 종사자의 평판과 명성에 위해를 가할 우려가 높으며 변호사나 의사의 경우 영업상 손해와 직결될 수 있다. 그러므로 본고는 전문직 종사자가 공적인 존재라는 특수한 지위를 지닐 경우 온라인 평가라는 표현의 자유와 전문직 종사자의 자기정보결정권의 법적 한계를 설정해야 하는 문제에 대하여 고찰하고자 한다. With the advancement of IT technology, the Cyber ​​Space, which is now formed through the Internet, a computer network, has replaced paperwork, which has been used as a representative medium of conventional public expression. In addition, the transmission of information and opinions in the cyberspace has a tendency to transcend time and space so that its power is not comparable to the tributaries, thus leading to maximization of freedom of expression. However, on the other hand, in the virtual space of cyberspace, a person's information is disclosed without his consent, and various crimes such as infringement of moral rights and privacy, malicious use of the information, It is getting bigger. As shown in the recent suicide cases of childcare teachers in Korea, professionals such as teachers are more likely to treat public individuals than private individuals in that they are professions requiring high public interest and morality. For this reason, professionals, including teachers, attorneys, and doctors, are in a position to disclose personal information for the public's right to know, even without the consent of the subject. In particular, it has been questioned in the case of Korea and Germany whether the public online evaluation of professional individuals is a legal interest that can be protected by freedom of expression and how the personal legal interests of the infringed individuals can be protected. Moreover, in the case of 'evaluation', an extremely subjective point of view may be intervened. Moreover, if an evaluation is carried out by adding arbitrary criteria of public or portal managers, even if they are engaged in a profession with a public interest, the evaluation result is accepted. Not easy to do In the case of the Internet, the media's specificity has a high risk of spreading and harming the reputation and reputation of professionals. In the case of lawyers and doctors, it can be directly related to business damage. Therefore, this paper examines the problem of setting the legal limits of the freedom of expression and the professionals' right to personal self-information when an expert individual has a special status of public existence. KCI Citation Count: 1